Pollen Morphology of Angiosperms of Central Nepal - Karna Mallick, Pushpa (International Journal of Applied Sciences and Biotechnology, 2019)
Morphological structures of pollen-grains of fifteen species of angiosperms collected from Central Nepal were cytologically carried out. Pollen structure of fifteen species viz. Antirrhium majus from family Plantaginaceae, Brunfelsia pauciflora and Petunia hybrida from Solanaceae, Centurea cyanus and Chrysanthemum morifolium from Asteraceae, Malvaviscous arboreus from Malvaceae, Lantana camera from Verbenaceae, Chlorophytum comosum from Asperagaceae, Oxalis europia from Oxilidaceae, Jasminum officinale from Oleaceae, Geranium roseous from Geranaceae, Mirabilis jalapa from Nyctaginaceae, Phlox paniculata from Polymoniaceae and Tradescantia brivifolia from commelinaceae studied in this investigation. Most of the structure of pollen found to be spheroidal, some irregular, oval, elongated and circular. The present study gives an account of variations of pollen grain structure within the angiosperms family. Triporate to polyprate aperture and echinate to smooth walled exine were observed in present study. Pollen morphology of the angiosperm is significantly helpful at the generic and specific level in plant taxonomy. Int. J. Appl. Sci. Biotechnol. Vol 7(1): 102-107